Fundamentals of wireless networking - Price, Ron, 1947- (New York : McGraw Hill/Irwin, 2007)
Addressing a fast emerging curriculum, Fundamentals of Wireless Networking provides a fundamental introduction to wireless networking for students who have little experience working on local area networks. Providing a straightforward survey of wireless technologies, the book is designed to also provide practical, hands-on experience that will build skills required of wireless network technicians. Key wireless topics, such as radio frequency communications, wireless hardware devices, and IEEE standards are explained in a straightforward, easy-to-read style. Ron Price is a teacher who has extensive experience designing and implementing wireless networks.
Includes index.v
1
Keywords: Wireless LANs; Wireless communication systems